Factors associated with numbers of remaining teeth among type 2 diabetes: a cross‐sectional study. Issue 13 (8th May 2013) - Huang, Jui‐Chu; Peng, Yun‐Shing; Fan, Jun‐Yu; Jane, Sui‐Whi; Tu, Liang‐Tse; Chang, Chang‐Cheng; Chen, Mei‐Yen
<x xml:space="preserve">Abstract</x> Aims and objectives To explore the factors associated with the numbers of remaining teeth among type 2 diabetes community residents. Background Promoting oral health is an important nursing role for patients with diabetes, especially in disadvantaged areas. However, limited research has been carried out on the relationship between numbers of remaining teeth, diabetes‐related biomarkers and personal oral hygiene among diabetic rural residents. Design A cross‐sectional, descriptive design with a simple random sample was used. Methods This study was part of a longitudinal cohort study of health promotion for preventing diabetic foot among rural community diabetic residents. It was carried out in 18 western coastal and inland districts of Chiayi County in central Taiwan. In total, 703 participants were enrolled in this study. Results The findings indicated that a high percentage of the participants (26%) had no remaining natural teeth. Nearly three quarters (74%) had fewer than 20 natural teeth. After controlling for the potential confounding factors, multivariate analysis demonstrated that the factors determining numbers of remaining teeth were age (p < 0·001), education (p < 0·001), using dental floss (p = 0·003), ankle brachial pressure index (p = 0·028), waist circumference (p = 0·024) and HbA1C (p = 0·033). Conclusions Except for some unmodifiable factors, the factors most significantly associated with numbers of remaining teeth were less tooth‐brushing with dental floss, abnormal ankle brachial pressure and poor glycemic control. Relevance to clinical practice This study highlights the importance of nursing intervention in oral hygiene for patients with type 2 diabetes. It is necessary to initiate oral health promotion activities when diabetes is first diagnosed, especially for older diabetic residents of rural or coastal areas who are poorly educated.